B cell subpopulations and their role in the pathogenesis of primary Sjögren’s syndrome: insights from single-cell RNA sequencing - Zhang, Xiaoyu; Han, Yuanwei; Zhang, Jing; Song, Yu; Zhou, Yan; Wang, Jia; Tian, Jinhai; Xin, Xinran; Liu, Bin; Fang, Li; Zhu, Hong (Frontiers in Immunology, 2025)
ObjectiveThis study aims to investigate the potential role of B cells in the pathogenesis of Primary Sjögren’s Syndrome (pSS) by analyzing cell types, differentially expressed genes, and associated signaling pathways using single-cell RNA sequencing.MethodsPeripheral blood mononuclear cells (PBMCs) from 3 pSS patients and 3 healthy controls (HCs) were collected. Single-cell transcriptomic analysis was performed, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, transcription factor analysis, pseudotime analysis, cell communication analysis, and B cell receptor (BCR) repertoire analysis. Genes and pathways potentially involved in the pathogenesis of pSS were identified, and key genes were validated by qRT-PCR. Statistical significance was assessed using T-tests and the Wilcoxon rank-sum test, with a p-value < 0.05 considered statistically significant.ResultsSingle-cell RNA sequencing of peripheral blood B cells from three patients with primary Sjögren’s syndrome (pSS) and three healthy controls (HCs) identified three subpopulations: memory B (Bmem), naïve B (NaiveB), and plasma cells (PlasmaCells). In pSS, differentially expressed genes were enriched in Type I interferon signaling, antigen processing/presentation, and MHC class II binding. Transcription factors related to interferon responses, including NR2F6, IRF5, STAT2, and IRF9, were upregulated. Cell–cell communication analysis highlighted frequent interactions via TNFSF10–TNFRSF10C and TGFB1–TGFBR3. Pseudotime analysis indicated accelerated NaiveB differentiation along the effector branch. B cell receptor repertoire analysis revealed increased IGHV4-34 usage and higher IGHJ4/IGHJ6 usage in PlasmaCells, with reduced IGHV1-3, IGHV1-69D, and IGHV2-7D usage. qRT-PCR validation in 22 pSS patients and 22 HCs confirmed significant ISG15 upregulation (p < 0.0001).ConclusionB cells contribute to the pathogenesis of pSS through the Type I IFN signaling pathway mediated by genes such as ISG15, alterations in BCR clonality, IGHV-J gene rearrangements, and abnormal gene usage.